Death comes silently [large type] - Hart, Carolyn G. (Hart, Carolyn G. Death on demand series., 2012)
Annie Darling, owner of the mystery bookstore Death on Demand, jumps at the chance to host a book signing with a local writer. But since it conflicts with her shift at the charity shop Better Tomorrow, Annie asks fellow volunteer Gretchen Burkholt to sub for her. The signing goes well, but Gretchen leaves several voice mails about scandalous news she's dying to share. Annie heads over to Better Tomorrow after the signing - and finds Gretchen murdered.